Chinese General Yue Fei: Martial Arts Facts, Tales, and Mysteries - Stanley E. Henning (Universidad de León, 2012)
Yue Fei (1103-1142), the famous Southern Song dynasty general who successfully resisted Jin (Jurched) incursions until he was murdered at the age of 39 as a result of court intrigues, has been credited with a number of boxing schools. While the historical record has not supported these relationships, there were reasons for the myths, which have persisted to the present. This article clarifies the Yue Fei-martial arts connection by use of original Chinese historical materials, including Yue Fei's biographical record, and a visit to the Yue Fei Temple in Hangzhou. It confirms Yue Fei's known martial arts skills and explains the factors behind his recognition as one of China's most revered patriots and martial arts symbols.